CSR Towards Workplace and Human Resource Disclosure: Employees' Perspectives / Yusniyati Yusri and Azlan Amran. - Yusri, Yusniyati; Amran, Azlan (Universiti Teknologi MARA Cawangan Selangor, 2012)
This paper explores employee's understanding on the concepts of Corporate Social Responsibility (CSR) and their perceptions towards disclosure of workplace and human resource information. Twenty three employees from various levels and functions from eight Public Listed Companies (PLCs) in Malaysia were interviewed to gain their understanding on the concepts of CSR and their perceptions on the importance of company's workplace and human resource disclosure. The results show that employees' understanding of CSR are more on the involvement of company in society, community and environmental activities. The study also revealed a large potential of good positive effects for company to voluntarily disclose workplace and human resource information such as increased company image to the public as well as good recruitment policy and strategy for the company in getting and retaining talented staffs. As for social responsibility disclosure (SRD), employees did not really appreciate disclosure in annual reports as they fully utilised the information through the medium of internal communication such as email, company portal, bulletin and magazine.